The Unsafe Acts and the Decision-to-Err Factors of Thai Construction Workers - Aksorn , Thanet; Hadikusumo, B.H.W. (Penerbit Universiti Sains Malaysia, 2007)
The unsafe acts of workers are considered as major contributors of work-related accidents and injuries on construction sites. However, not much work has been done to address the reasons why unsafe acts of workers occur particularly in construction industry. The aim of this paper therefore, is to investigate the major unsafe acts (i.e., at-risk behavior), and the decision-to-err factors causing unsafe acts. A questionnaire survey was conducted to collect data from a total of 214 workers from 20 building construction projects in Thailand. The findings revealed that the failure of workers to wear personal protective equipment (PPE), improper lifting or handling of materials, and keeping sharp objects in dangerous locations, are the major unsafe acts which frequently occur on construction sites in Thailand. In addition, the paper reported that the top three most frequent unsafe acts are statistically associated with several decision-to-err factors, including lack of management support, management pressure, group norms, overconfidence, being uncomfortable, past experience and laziness.